Oral subchronic exposure to silver nanoparticles in rats. (June 2016) - Garcia, Tania; Lafuente, Daisy; Blanco, Jordi; Sánchez, Domènec J.; Sirvent, Juan J.; Domingo, José L.; Gómez, Mercedes
Abstract: Because of their extremely small size, silver nanoparticles (AgNPs) show unique physical and chemical properties, with specific biological effects, which make them particularly attractive for being used in a number of consumer applications. However, these properties also influence the potential toxicity of AgNPs. In this study, we assessed the potential toxic effects of an in vivo oral sub-chronic exposure to polyvinyl pyrrolidone coated AgNPs (PVP-AgNPs) in adult male rats. We also assessed if oral PVP-AgNPs exposure could alter the levels of various metals (Fe, Mg, Zn and Cu) in tissues. Rats were orally given 0, 50, 100 and 200 mg/kg/day of PVP-AgNPs. Silver (Ag) accumulation in tissues, Ag excretion, biochemical and hematological parameters, metal levels, as well as histopathological changes and subcellular distribution following PVP-AgNPs exposure, were also investigated. After 90 days of treatment, AgNPs were found within hepatic and ileum cells. The major tissue concentration of Ag was found in ileum of treated animals. However, all tissues of PVP-AgNPs-exposed animals showed increased levels of Ag in comparison with those of rats in the control group. No harmful effects in liver and kidney, as well as in biochemical markers were noted at any treatment dose. In addition, no hematological or histopathological changes were found in treated animals. However, significant differences in Cu and Zn levels were found in thymus and brain of PVP-AgNPs-treated rats. Highlights: We investigated in rats the potential toxic effects of oral PVP-AgNPs. After 90 days of treatment, AgNPs were found within hepatic and ileum cells. No harmful effects in liver and kidney, as well as in biochemical markers were noted at any treatment dose. PVP-AgNPs could alter Zn and Cu levels in thymus and brain of treated animals.